THE IMPLEMENTATION OF OPEN-INQUIRY APPROACH TO IMPROVE STUDENTS' LEARNING ACTIVITIES, RESPONSES, AND MATHEMATICAL CREATIVE THINKING SKILLS - Kadir, Kadir; Lucyana, Lucyana; Satriawati, Gusni (Journal on Mathematics Education, 2017)
This study aims to reveal the improvement of the students’ learning activities, responses, and mathematical creative thinking skills (MCTS) through open- inquiry approach (OIA). Other relevant studies in mathematics learning tend to focus on guided inquiry, and especially in Indonesia, OIA is still less applied. This study is conducted at State Junior High School in Indonesia. The method used in this study is Classroom Action Research (CAR) consists of four stages: planning, acting, observing, and reflecting. Data is collected through observation, journal reviews, interview, and test. The result of the study shows that the implementation of OIA enhances the students’ MCTS. It is shown by the improvement of the average of students’ score from 73.05 in the first cycle to 78.95 in the second cycle. The increasing of MCTS includes some aspects: fluency, flexibility, and originality. The result also shows that in general, the students give positive response and engage well in learning activities with OIA. It can be concluded that the implementation of OIA enhances learning activities, gives positive response towards mathematics, and improves students’ creative thinking skills.Keywords: Open-Inquiry Approach, Learning Activity, Response, Creative Thinking Skill DOI: http://dx.doi.org/10.22342/jme.8.1.3406.103-114